2010
DOI: 10.1002/ana.22023
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of aquaporin‐4 water channels after contusion spinal cord injury

Abstract: These results suggest that AQP4 plays a protective role after contusion SCI by facilitating the clearance of excess water, and that targeting edema after SCI may be a novel therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…Oshio et al found that AQP4 was intensely stained throughout the gray matter in spinal cord, especially in the capillary-surrounding astrocytic end-feet 19 . In particular, AQP4 and spinal cord edema are positively correlated 40,41 . AQP4 in spinal cord is expressed in glial cells throughout the gray matter and glial foot processes adjacent to the spinal capillary endothelium 19 .…”
Section: Discussionmentioning
confidence: 95%
“…Oshio et al found that AQP4 was intensely stained throughout the gray matter in spinal cord, especially in the capillary-surrounding astrocytic end-feet 19 . In particular, AQP4 and spinal cord edema are positively correlated 40,41 . AQP4 in spinal cord is expressed in glial cells throughout the gray matter and glial foot processes adjacent to the spinal capillary endothelium 19 .…”
Section: Discussionmentioning
confidence: 95%
“…For example, Kimura et al 23 have reported that AQP4 has a protective role after contusion SCI in mice. The differences between the study by Kimura et al and ours are likely to be due to the use of different animal species, injury models and severity of injury.…”
Section: Discussionmentioning
confidence: 99%
“…9 AQP4 is regarded to have essential roles to maintain BBB integrity in several models of CNS injuries, including spinal cord injury, subarachnoid hemorrhage and ICH. 11,30,31 Our previous study found AQP4 suppressed TJ opening and endothelial cell swelling after ICH when compared with the AQP4 À / À mice group. 11 In addition, AQP4 is believed to be involved in the protective effects of vascular endothelial growth factor (VEGF) and granulocyte colony-stimulating factor on BBB after ICH in our recent work.…”
Section: Erythropoietin Protects Bbb From Disruptionmentioning
confidence: 92%